Two-wavelength microscopic speckle interferometry using colour CCD camera - Upputuri, Paul K. (2015)
Single wavelength microscopic speckle interferometry is widely used for deformation, shape and non-destructive testing (NDT) of engineering structures. However the single wavelength configuration fails to quantify the large deformation due to the overcrowding of fringes and it cannot provide shape of a specimen under test. In this paper, we discuss a two wavelength microscopic speckle interferometry using single-chip colour CCD camera for characterization of microsamples. The use of colour CCD allows simultaneous acquisition of speckle patterns at two different wavelengths and thus it makes the data acquisition as simple as single wavelength case. For the quantitative measurement, an error compensating 8-step phase shifted algorithm is used. The system allows quantification of large deformation and shape of a specimen with rough surface. The design of the system along with few experimental results on small scale rough specimens is presented.